Aktivitas Antioksidan Fraksi Larut Etil Asetat dari Ekstrak Akar Tabar Kedayan (Aristolochia papilifolia Ding Hou) - Novermawati; Iswahyudi; Ahmad, Islamudin; Masruhim, Muhammad Amir (B-Creta Publisher, 2024)
Kedayan root is a medicinal plant that is traditionally used by the community as medicine, especially as an antidote to poison. This research aimed to determine the antioxidant activity of the ethyl acetate soluble fraction of Tabar Kedayan root extract (Aristolochia papillfolia Ding hou). The fractionation method used is solid-liquid extraction using ethyl acetate solvent to obtain a soluble fraction of ethyl acetate, then vacuum liquid chromatography fractionation using the eluent ratio n-hexane: ethyl acetate and obtain fraction A, fraction B, fraction C, fraction D, fraction E, fraction F. Testing of antioxidant activity using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method spectrophotometrically. The data obtained was analyzed using linear regression to determine IC50. The results of the C fraction test on the ethyl acetate soluble fraction of Tabar Kedayan roots (A. papillfolia) have antioxidant activity with an IC50 value of 139.11 ppm.